DIURETIC RESISTANCE AS A GENERAL CLINICAL PROBLEM - N. A. Mukhin; V. V. Fomin; A. A. Pulin (Сеченовский вестник, 2022)
Etiology, pathogenesis and treatment strategies in diuretic-resistant oedema are discussed